INFORMATION TECHNOLOGIES IN EDUCATION: APPLICATION OF STREAM TECHNOLOGIES - Kurbakova, Svetlana; Evgrafova, Irina; Zhanatayev, Kazakbay; Polozhentseva, Irina; Rabadanova, Raziуat (Revista Inclusiones, 2020)
The article deals with using stream learning information technology in the context of teaching students of humanitarian specialties. The authors consider the theoretical views of researchers on the stream learning features, the presentation of educational material using video materials, which is a didactic tool that increases the level of perception and understanding of teaching information. Based on the students’ survey, the authors have revealed their attitude to using the stream learning method, creating and using educational videos by teachers, as well as types of educational activities where it is advisable to use stream technologies in the educational process. The article considers also the advantages and disadvantages of using stream technologies in the educational process. The authors consider various types of videos, the possibilities of their use in the educational process, requirements for their preparation, recommendations for use, and options for combining with other multimedia.